Performance possibilities and limits in Indian surface irrigation - Basu, D. N.; Shirahatti, P. P. (International Food Policy Research Institute, 1990)
This chapter is presented in two parts. The first presents a brief overview of the performance of Indian irrigation systems and specifically discusses the use and limitations of performance indicators of an irrigation system. No detailed, project-specific findings are presented in the first part, although reference is made to such findings to illustrate the relevant performance indicator. A careful examination of the performance indicators normally used is a prerequisite for evaluating any irrigation system as well as evolving criteria for improved performance.